Priming Partisan Identities and Support for Political Violence - Kacholia, Suhan; Neuner, Fabian Guy (Frontiers in Political Science, 2022)
Individuals in the United States appear increasingly willing to support and justify political violence. This paper therefore examines whether making partisan identities salient increases support for political violence. We embed priming manipulations in a sample of roughly 850 U.S. adults to investigate whether activating positive partisan identity, negative partisan identity, instrumental partisan identity, and American national identity might lead to differences in reported support for political violence. While we uncover no effects of priming various identities on support for political violence, we replicate and extend previous research on its correlates. Specifically, we demonstrate how various measures of partisan identity strength as well as negative personality traits are correlated with acceptance of political violence.